ORIENTASI KHODAM DALAM PENDIDIKAN PESANTREN - Zen Amrullah; Akhmad Said (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2020)
The meaning of khodam in pesantren is another name for the help of the selfless Kiai, be it khadam bi al-tabarruk, bi al-Maqsud, which not everyone can become a Kiai khodam, they also help the Kiai in carrying out the duties of the pesantren and the housekeeping and economy for the sake of achieving a goal, namely getting blessings or benefits from a Kiai or teacher, although there are some khodam from outsiders who have never studied at the pesantren, khodam is an alternative for students who want to study at the pesantren but do not have sufficient costs to live it, so that by becoming a khodam, they can get an education with the help of their education costs by the Kiai. The view of the pesantren community regarding the existence of khodam basically, they are very helpful in the success of the educational process, with their existence, the students, ustad and even the general public find it easier to communicate with the caregiver or Kiai, Kiai sees khodam not as a marginalized santri, even, on the other hand, the khodam is already considered part of the pesantren's extended family so there is no difference between regular santri and santri who concurrently become this khodam.